A novel family of transcription factors conserved in angiosperms is required for ABA signalling. (27th September 2017) - Tian, Hainan; Chen, Siyu; Yang, Wenting; Wang, Tianya; Zheng, Kaijie; Wang, Yating; Cheng, Yuxin; Zhang, Na; Liu, Shanda; Li, Dongqiu; Liu, Bao; Wang, Shucai
Abstract: The plant hormone abscisic acid (ABA) plays a crucial role in regulating plant responses to environmental stresses. Interplay of several different proteins including the PYR/PYL/RCAR receptors, A‐group PP2C protein phosphatases, SnRK2 protein kinases, and downstream transcription factors regulates ABA signalling. We report here the identification of a family of ABA‐induced transcription repressors (AITRs) that act as feedback regulators in ABA signalling. We found that the expression of all the 6 Arabidopsis AITR genes was induced by exogenously ABA, and their expression levels were decreased in ABA biosynthesis mutant aba1‐5 . BLAST searches showed that AITRs are exclusively present in angiosperms. When recruited to the promoter region of a reporter gene by a fused DNA binding domain, all AITRs inhibited reporter gene expression in transfected protoplasts. In Arabidopsis, aitr mutants showed reduced sensitivity to ABA and to stresses such as salt and drought. Quantitative RT‐PCR analysis demonstrated that the ABA‐induced response of PP2C and some PYR / PYL / RCAR genes was reduced in AITR5 transgenic plants but increased in an aitr2 aitr5 aitr6 triple mutant. These results provide important new insights into the regulation of ABA signalling in plants, and such information may lead to the production of plants with enhanced resistance to environmental stresses. Abstract : ABA plays an important role in regulating plant responses to environmental stresses; however, positive feedback regulation loops of ABA signalling remained largely unknown. We identified ABA‐induced transcription repressors (AITRs) as a novel family of transcription factors, and we found that AITRs positively regulate ABA signalling and negatively regulate plant responses to environmental stresses in Arabidopsis. AITRs are evolutionarily conserved in angiosperms, thus may be attractive targets for genetic modification to enhance plant tolerance to environmental stresses.